Erosional and Tectonic Evolution of a Retroarc Orogenic Wedge as Revealed by Sedimentary Provenance: Case of the Oligocene – Miocene Patagonian Andes - Leonard, Joel S.; Fosdick, Julie C.; VanderLeest, Rebecca A. (Frontiers in Earth Science, 2020)
Sedimentary provenance techniques have been widely applied in foreland basin settings to understand tectonic and magmatic processes by tracking the exposure and erosion of distinct sediment source areas through time. We present a case example from the Magallanes-Austral retroarc foreland basin of Chile and Argentina (51°30’S), where modal sandstone and conglomerate compositional data, detrital zircon U-Pb geochronology, and sedimentology data from the Oligocene-Miocene Río Guillermo Formation document a change in source areas during an important stage of orogenic development. In particular, our results from the ~24.3-21.7 Ma Río Guillermo Formation record an abrupt shift from transitional to undissected arc provenance that indicate rejuvenated magmatism within the contemporary arc. Minor components of lithic grains suggest a subordinate source of recycled sediments that we interpret may have been derived from the intervening external fold-and-thrust belt, rather than directly from sources in the hinterland thrust domain. Detrital zircon U-Pb geochronology data show mostly Neogene (~20-40 Ma) and Cretaceous (~70-110 Ma) age groups, with minor amounts of Jurassic (~145-155 Ma) and Paleozoic (~260-540 Ma) age groups, which are consistent with a syndepositional arc and recycled external fold-and-thrust belt sources. Stratigraphic data suggest a vegetated, channelized braidplain environment developed above an erosional unconformity with the underlying shallow-marine Río Turbio Formation. Upsection, the Río Guillermo Formation locally transitions to a low-energy, organic-rich floodplain setting located within the upper reaches of a fluvial-tidal transition zone of the coastal plain, and the uppermost part of the formation is characterized by a coarse-grained sandy channelized braidplain environment along the foreland basin margin. Moderate sediment accumulation rates and coastal plain progradation during this period is consistent with sustained sediment flux from the Patagonian Andes and tectonic subsidence along the basin margin. Taken collectively, we propose that the abrupt provenance shift dominantly records erosion of the rejuvenated mafic volcanic arc, despite coeval changes in orogenic wedge dynamics brought about by increased plate convergence rates that drove uplift of the intervening external-fold-and-thrust belt along reactivated deep-seated high-angle basin structures.